The First Three Seconds: a Review of Possible Expansion Histories of the Early Universe - Allahverdi, Rouzbeh; Amin, Mustafa A.; Berlin, Asher; Bernal, Nicholas; Byrnes, Christian T.; Delos, M. Sten; Erickcek, Adrienne L.; Escudero, Miguel; Figueroa, Daniel G.; Freese, Katherine; Harada, Tomohiro; Hooper, Dan; et al. (The open journal of astrophysics, 2021)
It is commonly assumed that the energy density of the Universe was dominated by radiation between reheating after inflation and the onset of matter domination 54,000 years later. While the abundance of light elements indicates that the Universe was radiation dominated during Big Bang Nucleosynthesis (BBN), there is scant evidence that the Universe was radiation dominated prior to BBN. It is therefore possible that the cosmological history was more complicated, with deviations from the standard radiation domination during the earliest epochs. Indeed, several interesting proposals regarding various topics such as the generation of dark matter, matter-antimatter asymmetry, gravitational waves, primordial black holes, or microhalos during a nonstandard expansion phase have been recently made. In this paper, we review various possible causes and consequences of deviations from radiation domination in the early Universe - taking place either before or after BBN - and the constraints on them, as they have been discussed in the literature during the recent years.